Islam, politics, anthropology - Osella, Filippo; Soares, Benjamin F. (Chichester, West Sussex, [England] Wiley-Blackwell, 2010)
Islam, Politics, Anthropology offers critical reflections on past and current studies of Islam and politics in anthropology and charts new analytical approaches to examining Islam in the post-9/11 world.
Islam, politics, anthropology / Benjamin Soares & Filippo Osella -- Being good in Ramadan : ambivalence, fragmentation, and the moral self in the lives of young Egyptians / Samuli Schielke -- Doubt, faith, and knowledge : the reconfiguration of the intellectual field in post-Nasserist Cairo / Hatsuki Aishima & Armando Salvatore -- A tour not so grand : mobile Muslims in northern Pakistan / Magnus Marsden -- Muslim politics in postcolonial Kenya : negotiating knowledge on the double-periphery / Kai Kresse -- Between dialogue and contestation : gender, Islam, and the challenges of a Malian public sphere / Rosa De Jorio -- Piety politics and the role of a transnational feminist analysis / Lara Deeb -- Mukadas's struggle : veils and modernity in Kyrgyzstan / Julie McBrien -- Genealogy of the Islamic state : reflections on Maududi's political thought and Islamism / Irfan Ahmad -- Talking jihad and piety : reformist exertions among Islamist women in Bangladesh / Maimuna Huq -- Market Islam in Indonesia / Daromir Rudnyckyj -- Muslim entrepreneurs in public life between India and the Gulf : making good and doing good / Filippo Osella & Caroline Osella -- Islam and the politics of enchantment / Gregory Starrett.
Originally published as vol. 15, special issue, May 2009 of The Journal of the Royal Anthropological Society.
Keywords: Political anthropology -- Islamic countries; Islam and politics; Islam and culture; Politics and culture -- Islamic countries; Islamic countries -- Politics and government